Parental Help-Giving Orientations Scale (PHGOs) in Children’s Learning: Construction and Validation - Yael Grinshtain; Gal Harpaz; Yosi Yaffe (Education Sciences, 2023)
Parental involvement in the education and learning processes of children in general has become central in the last few decades. Following this involvement, the home arena is considered highly influential in providing a supportive environment for children’s learning processes. Help-giving orientations of parents to their children in relation to homework and learning assignments can be crucial for the children’s futures. According to the Help Relations theory regarding the two main orientations—dependent versus autonomy help (dependent help-giving rather than autonomy help), prevents opportunities to develop autonomous coping abilities in future. The Parental Help-Giving Orientations scale was designed to measure parental help to their children in learning at home. In Study 1, eleven experts evaluated orientations of parental help-giving that emerged from interviews. In Study 2 (n = 255), exploratory factor analyses (EFA) indicated four reliable factors: autonomic, dependent reminder, dependent partner, and dependent student. The confirmatory factor analysis (CFA) in Study 3 in an independent sample of parents (n = 303) exhibited a good model-fit of the data and demonstrated measurement invariance across parental gender. The scale can be used to measure individual differences in orientations in help-seeking among mothers and fathers.